MYB pathways that regulate UV-B-induced anthocyanin biosynthesis in blueberry (Vaccinium corymbosum) - Song, Yan; Ma, Bin; Guo, Qingxun; Zhou, Lianxia; Zhou, Xintong; Ming, Ziqing; You, Honglin; Zhang, Chunyu (Frontiers in Plant Science, 2023)
Ultraviolet-B (UV-B) promotes anthocyanin accumulation and improves fruit quality in plants. To explore the underlying network of MYB transcription factors that regulates UV-B-induced anthocyanin biosynthesis in blueberry (Vaccinium corymbosum), we analyzed the response of MYB transcription factor genes to UV-B treatment. Transcriptome sequencing analysis revealed that VcMYBA2 and VcMYB114 expression were downregulated and were positively correlated with the expression of anthocyanin structural genes under UV-B radiation according to weighted gene co-expression network analysis (WGCNA) data. The VcUVR8-VcCOP1-VcHY5 pathway perceives UV-B signals and promotes the expression of anthocyanin structural genes by upregulating VcMYBA2 and VcMYB114 or by regulating the VcBBXs-VcMYB pathway, ultimately promoting anthocyanin accumulation. By contrast, VcMYB4a and VcUSP1 were downregulated under UV-B treatment, and VcMYB4a expression was negatively correlated with that of anthocyanin biosynthesis genes in response to UV-B. Analysis of VcMYB4a-overexpressing and wild-type blueberry calli exposed to UV-B radiation revealed that VcMYB4a represses UV-B-induced anthocyanin accumulation. Yeast one-hybrid and dual luciferase assays showed that the universal stress protein VcUSP1 directly bound to the promoter of VcMYB4a. These results suggest that the VcUSP1-VcMYB4a pathway negatively regulates UV-B-induced anthocyanin biosynthesis and provide insight into UV-B-induced anthocyanin biosynthesis.